Demystifying the "Dark Side of the Knee": An Update on Imaging of the Posterolateral Corner - Castro, Miguel Oliveira; Baptista, Diogo Correia; Afonso, P Diana (Seminars in musculoskeletal radiology, 2024)
The posterolateral corner (PLC) of the knee is a complex anatomical-functional unit that includes ligamentous and tendinous structures that are crucial for joint stability. This review discusses the intricate anatomy, biomechanics, and imaging modalities, as well as the current challenges in diagnosing PLC injuries, with an emphasis on magnetic resonance imaging (MRI). Recognizing the normal MRI anatomy is critical in identifying abnormalities and guiding effective treatment strategies. Identification of the smaller structures of the PLC, traditionally difficult to depict on imaging, may not be necessary to diagnose a clinically significant PLC injury. Injuries to the PLC, often associated with cruciate ligament tears, should be promptly identified because failure to recognize them may result in persistent instability, secondary osteoarthritis, and cruciate graft failure.